The music archive of the 20th century - Carballar, Diego (2023)
The article examines a pedagogical experience that became a theoretical and analytical methodological inquiry. Although the starting point was the texts presented in an arbitrary series (that of the letter B), this principle (this restriction) was soon extended to the musical corpus of the twentieth century. The work plan, which we called «Archival good», aimed to find in a limited space of experimentation the fundamental lines of art (and aesthetic politics) of the 20th century.